2019
DOI: 10.1016/j.techfore.2019.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Does the utilization of information communication technology promote entrepreneurship: Evidence from rural China

Abstract: Impacts on the probability of transition to entrepreneurship in rural China associated with the utilization of information communication technology (ICT) are estimated using longitudinal data from the China Family Panel Studies (CFPS) survey. We identify cell phone ownership and internet use as proxy variables for ICT utilization and find that cell phone ownership and internet use have positive impacts on entrepreneurship. After controlling for observables and time and regional fixed effects, cell phone users … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(53 citation statements)
references
References 53 publications
1
52
0
Order By: Relevance
“…The CFPS covers 95% of the Chinese population in 25 provinces, providing extensive individual- and family-level economic and social life information. The data from CFPS has been validated and used for research in entrepreneurship ( Barnett et al., 2019 ) and other fields ( Hou et al., 2020 ; Sun et al., 2020 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The CFPS covers 95% of the Chinese population in 25 provinces, providing extensive individual- and family-level economic and social life information. The data from CFPS has been validated and used for research in entrepreneurship ( Barnett et al., 2019 ) and other fields ( Hou et al., 2020 ; Sun et al., 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…A social network refers to a network of friends and acquaintances tied with formal and informal connections ( Barnett et al., 2019 ), that can exist both online and offline. Social media is useful for creating, expanding and managing networks.…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies (Bandera, Collins, & Passerini, 2018;Cujia Berrio, Redondo, & Hernández, 2018;Barnett, Hu, & Wang, 2019) have found that the use of ICT has positive effects on entrepreneurs, is stimulating them and is moderating the relationship between entrepreneurial attitudes and risk. Moreover, the increase in information available due to new technologies positively affects aggregate entrepreneurship in national economies (Hanoteau & Rosa, 2019).…”
Section: Literature Reviewmentioning
confidence: 97%
“…An increasing number of researches (including Bandera, Collins, & Passerini, 2018;Cujia Berrio, Redondo, & Hernández, 2018;Barnett, Hu, & Wang, 2019;Hanoteau & Rosa, 2019) have argued for positive and significant influence of the adoption and implementation of ICTs on entrepreneurship. The Global Entrepreneurship Monitor also suggested that information technologies explain a large portion of the increase in opportunity motivated entrepreneurship, and a greater access to ICTs may encourage entrepreneurs to be more innovative (GEM, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%